Analysis of Financial Inclusion in UMKM Medan City: A Review of Sharia Economics - Ujung, Asna Ul Husni; Nurbaiti, Nurbaiti; Tambunan, Khairina (Amkop Management Accounting Review (AMAR), 2025)
Financial inclusion is the ability of the community to access various financial institutions, products and services according to the needs and capabilities of the community. The purpose of this study is to analyze the financial inclusion of MSMEs in Medan City related to the obstacles faced in accessing financing from formal financial institutions, analyze the understanding of financial literacy, and the understanding in accessing technology/fintech that can increase financial inclusion. This study uses a qualitative approach with descriptive analysis. The findings of the study show that there are MSMEs in Medan City who have not had access to formal financial services, a basic understanding of financial literacy, and the adoption and optimal use of digital/fintech payment systems are still challenges for MSME actors.